Antibiotic resistance of Helicobacter pylori in Australia and New Zealand: A systematic review and meta‐analysis. Issue 6 (3rd January 2021) - Schubert, Jonathon P; Gehlert, Jessica; Rayner, Christopher K; Roberts‐Thomson, Ian C; Costello, Sam; Mangoni, Arduino A; Bryant, Robert V
Abstract: Objective: While the global prevalence of antibiotic‐resistant Helicobacter pylori ( H. pylori ) is increasing, there is much regional variation, and local data are required to guide eradication therapy. We performed a systematic review and meta‐analysis to determine rates of H. pylori antibiotic resistance in Australia and New Zealand. Study Design: Random effects meta‐analysis of data from 15 published studies and three published abstracts reporting prevalence of primary or secondary H. pylori antibiotic resistance in Australasia. Data Sources: PubMed, EMBASE, MEDLINE, PROSPERO, and the Cochrane Library were searched until August, 2020. Data Synthesis: Fifteen published studies and three published abstracts were identified; one study was excluded due to high risk of bias. Seventeen studies conducted between 1996 and 2013 were included in the final analysis, 12 reporting primary and five reporting secondary antibiotic resistance. Prevalence of primary resistance was clarithromycin 7.4% (95% confidence interval [CI], 5.3–9.7%), metronidazole 50.0% (95%CI, 23.9–56.1%), fluoroquinolones 3.7% (95%CI, 0.004–14.8%), and both amoxicillin and tetracycline <0.5%. Subgroup analysis (last 20 years) showed doubling of clarithromycin resistance to 16.1% (95%CI 11.2–21.7%) with other resistance stable. Prevalence of secondary resistance was high for all antibiotics, particularly clarithromycin 78.7% (95%CI, 64.1–90.1%) and metronidazole 68.3% (95%CI, 59.9–76.1%). Conclusions: The outcomes reveal an increase in primary H. pylori clarithromycin resistance since the year 2000, while metronidazole resistance has remained stable and primary resistance to amoxicillin, tetracycline, and fluoroquinolones is low. Rates of secondary resistance to metronidazole and clarithromycin are high. The results highlight the need for contemporary local data on antibiotic resistance in Australia and New Zealand.